APLIKASI PUPUK CAIR TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN BAYAM MERAH (Amaranthus sp) - Roni ., Wakerkwa; Wenny ., Tilaar; Jeany Sh. Polii-Mandang (AGRI-SOSIOEKONOMI, 2017)
The purpose of this study is to determine the effect of growth and production of red spinach plants on Bayfolan fertilizer, and to obtain the appropriate dose of Bayfolan fertilizer for the growth and production of red spinach plants. The study was conducted from May to July 2017, in the beautiful Canaan Village VI, RT 02 Wanea District, Manado City, North Sulawesi Province. This research uses RAL Complete RAL Design with six treatment levels that is: R0 = 0 without treatment of Bayfolan fertilizer as control, R1 = 1 cc of Bayfolan / l water fertilizer, R2 = 2 cc of Bayfolan / l water fertilizer, R3 = 3 cc of Bayfolan / l water R4 = 4 cc of Bayfolan / l water fertilizer, R5-5 cc of Bayfolan / l water fertilizer, repeated four times. The dose of Bayfolan fertilizer does not affect the plant height, the number of leaves, the weight of the fresh vegetable tree. Fresh weight of leaves, root weight, and Root length. The results showed that the best Bayfolan fertilizer dose was 4 cc of Bayfolan / l water fertilizer.